2020
DOI: 10.1016/j.sjbs.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Morin attenuates STZ-induced diabetic retinopathy in experimental animals

Abstract: Diabetic retinopathy (DR) occurs in untreated diabetic patients due to the strong influence of oxidative stress. Bioflavonoids are well known for their antioxidant property. Morin, a bioflavonoid, has been demonstrated for its antioxidant as well as antidiabetic activity. Thus, this research work intended to determine the ameliorative impact of morin in DR rats using STZ-induced type 1 diabetic model. To induce type 1 diabetic in rats STZ (60 mg/kg) was administered intraperitoneally. Grouping of animals was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Among the compounds (morin, phloroglucinol, and 1-hexylbenzene) isolated from E. umbellata berries antioxidant morin has been assessed for antidiabetic potential. Morin, a bioflavonoid, has demonstrated antioxidant as well as antidiabetic activities along with its antihyperlipidemic effects in streptozotocin-induced diabetic rats [ 17 ]. Reported studies have revealed that morin can be used as a non-competitive inhibitor that regulates the expression of MicroRNA-29a (regulator of insulin receptor) in HepG2 cells and improves insulin signaling and stimulating the metabolic pathways [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the compounds (morin, phloroglucinol, and 1-hexylbenzene) isolated from E. umbellata berries antioxidant morin has been assessed for antidiabetic potential. Morin, a bioflavonoid, has demonstrated antioxidant as well as antidiabetic activities along with its antihyperlipidemic effects in streptozotocin-induced diabetic rats [ 17 ]. Reported studies have revealed that morin can be used as a non-competitive inhibitor that regulates the expression of MicroRNA-29a (regulator of insulin receptor) in HepG2 cells and improves insulin signaling and stimulating the metabolic pathways [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS induces lipid peroxidation in phospholipid-containing cell membranes, resulting in the production of MDA, which directly causes cytotoxicity and then induces ferroptosis [20]. Previous studies have demonstrated GSH depletion [21], ROS accumulation, and increased MDA production [10] in the retinas of diabetic rats. Our study showed that ROS content was obviously increased in HG-induced 661W cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ferroptosis has been found to play an important role in the progression of diabetes mellitus and its multiple complications, such as diabetic nephropathy, diabetic neuropathy, diabetic cardiomyopathy, and DR [7]. Previous studies have demonstrated that iron overload [8], glutathione (GSH) depletion [9], and lipid peroxidation product malondialdehyde (MDA) accumulation [10], the critical factors that trigger ferroptosis, promote the development and progression of DR. In addition, high glucose 2 of 16 (HG) administration has been confirmed to induce ferroptosis in human retinal capillary endothelial cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, apigenin improves diabetesassociated nephropathy in streptozotocin-induced diabetic rats as compared to control animals and prevents renal dysfunction, oxidative stress, inflammation, collagen deposition, glomerulosclerosis, and fibrosis (189). A promising anti-diabetic effect characterizes also other flavonoids like quercetin (190), morin (191), hesperetin (192), and kaempferol (193) as demonstrated in various diabetic animal models.…”
Section: Flavonoids Improve Hyperglycemia and Diabetesmentioning
confidence: 98%